2004
DOI: 10.1111/j.0001-6349.2005.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternity wards or emergency obstetric rooms? Incidence of near‐miss events in African hospitals

Abstract: Near-miss events are extremely common in some African hospitals, with a high proportion arriving in critical conditions. Near-miss events must be estimated separately for those already in a critical condition on arrival and those developing after admission; the first as a good indicator of the effectiveness of emergency referrals and the second as a potential tool for monitoring the performance of obstetric services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 7 publications
5
56
0
1
Order By: Relevance
“…We created a matrix with separate columns for early and late stages of pregnancy, and color-codes for marital status, for whether the severe obstetric complications arose prior or at arrival to the facility, and if care had been sought repeatedly. Separating near-miss events upon and after arrival helped to facilitate the distinction between potential pre-facility barriers and quality of care [24, 29]. We compared the overall similarities and differences of women’s narratives and field observations, and noted resemblances and contrasts in trajectories and experiences of care.…”
Section: Methodsmentioning
confidence: 99%
“…We created a matrix with separate columns for early and late stages of pregnancy, and color-codes for marital status, for whether the severe obstetric complications arose prior or at arrival to the facility, and if care had been sought repeatedly. Separating near-miss events upon and after arrival helped to facilitate the distinction between potential pre-facility barriers and quality of care [24, 29]. We compared the overall similarities and differences of women’s narratives and field observations, and noted resemblances and contrasts in trajectories and experiences of care.…”
Section: Methodsmentioning
confidence: 99%
“…(14) Studies from developing countries especially in the African region have reported a high incidence of near miss when compared to the developed world as can be seen from Table 2. (16171819202122232425262728) There are not many studies available from India on maternal near miss as is evident from Table 2.…”
Section: Prevalence Of Maternal Near Missmentioning
confidence: 99%
“…Although the objective criteria for defining severe maternal morbidity vary between studies, its prevalence ranges from 0.05%-1.7% in developed countries[34] and 0.6%-8.5% in resource-limited countries. [56] Critical care services are important for this subset of obstetric patients and critical care unit (CCU) admission may be considered as an objective marker of severe maternal morbidity. [78]…”
Section: Introductionmentioning
confidence: 99%